Pengembangan Media Pembelajaran Komik Eksperimen Fisika Berbasis Kearifan Lokal Untuk Sekolah Menengah Pertama - Jumadi Jumadi; I wayan Darmadi; Darsikin Darsikin (Media Eksakta, 2021)
This study aims to produce a physics experiment comic media based on local wisdom. This research uses 4D model development, which starts with defining the material, designing the media to becoming a product. After becoming a product, it is then validated by material experts and media experts. The comics that have been validated by several experts are then revised by the researchers with reference to the suggestions given by the validators. To make this comic, the researcher used Photoshop and Coreldraw X7 applications. This experimental comic is designed so that students can do simple experiments outside of school independently on temperature and heat material, besides that this comic displays the icon of the city of Palu and the story that develops on the icon. The research subjects of the feasibility test of this physics experiment comic were the seventh grade students of SMP Labschool Palu. The average score obtained is 3.71 with a very good category. The results of the study indicate that this experimental comic can be used as a learning medium.